2018
DOI: 10.1111/1744-9987.12695
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Expression of Circulating microRNAs in Systemic Lupus Erythematosus Patient Blood Plasma After Passing Through a Plasma Adsorption Membrane

Abstract: MicroRNAs (miRNAs, miRs) are small non-coding RNAs that mainly function in the post-transcriptional regulation of genes. miRNA that is secreted outside of cells, and which circulates in the peripheral blood, is called circulating microRNA. Systemic lupus erythematosus (SLE) is a typical autoimmune connective tissue disease and is mainly treated with immunosuppressive drugs. Therapeutic apheresis is often used to eliminate autoantibodies and cytokines. We have previously shown that circulating miRNAs in the blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…For the important role of extracellular RNA in lupus pathogenesis, the expression declined after effective therapy. SLE patient plasma miR-6088, miR-4732-5p and miR-1246 were significantly decreased after passage through the plasma adsorption membrane [93]. Mesenchymal stem cells (MSC) showed encouraging potential for lupus treatment.…”
Section: Extracellular Rna and Sle Treatmentmentioning
confidence: 99%
“…For the important role of extracellular RNA in lupus pathogenesis, the expression declined after effective therapy. SLE patient plasma miR-6088, miR-4732-5p and miR-1246 were significantly decreased after passage through the plasma adsorption membrane [93]. Mesenchymal stem cells (MSC) showed encouraging potential for lupus treatment.…”
Section: Extracellular Rna and Sle Treatmentmentioning
confidence: 99%
“…The DEmiRNAs investigated in the present study, some of which have been reported in previous studies, regulate the expression of protein-coding genes and affect several biological functions, serving a role in the occurrence and development of diseases. Studies have shown that miR-1246 may be involved in the development of autoimmune diseases and acts as a transfer messenger that leads to DNA damage by directly inhibiting the ligase 4 gene ( 26 , 27 ). The plasma expression levels of miR-1246 has been used as a diagnostic biomarker for hepatocellular carcinoma ( 28 , 29 ), and miR-1246 regulates the progression of breast and prostate cancer, highlighting the potential of miR-1246 in miRNA-based therapies ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…These miRNA "information packages" have recently been shown to be sequestered into extracellular, lipophilic microvesicles or exosomes that shuttle between cells and tissues and/or amongst ECF, CSF and blood serum compartments (Alexandrov et al, 2013;Jaber et al, 2017Jaber et al, , 2019Badhwar and Haqqani, 2020;Bitetto and Di Fonzo, 2020;Upadhya et al, 2020;Vanherle et al, 2020). Extracellularly secreted miRNAs circulating in the peripheral blood are referred to as "circulating miRNAs"; they are either encapsulated by extracellular vesicles such as exosomes and microvesicles, or bound to molecules such as the Argonaute protein, or HDL cholesterol (Zernecke et al, 2009;Arroyo et al, 2011;Vickers et al, 2011;Ishibe et al, 2018;Groot and Lee, 2020;Upadhya et al, 2020). In addition, miRNAs that leak from destroyed cells and apoptotic bodies are also found among circulating serum miRNAs and have been implicated in the spreading of AD neuropathology (Zernecke et al, 2009;.…”
Section: Overview Of Mirna Abundance In Ad Tissues and Biofluid Compamentioning
confidence: 99%
“…In addition, miRNAs that leak from destroyed cells and apoptotic bodies are also found among circulating serum miRNAs and have been implicated in the spreading of AD neuropathology (Zernecke et al, 2009;. It is also noteworthy to point out that while the ECF, CSF and blood serum can be considered as relatively contiguous biofluids, there may be selective biophysical barrier-mediated effects on miRNA permeability, translocation and trans-membrane transport of microRNAs which ends up as having the ECF, CSF, and blood serum compartments essentially distinct in their miRNA content and stoichiometric abundance (Blennow et al, 2010;Alexandrov et al, 2013;Hampel et al, 2018a,b,c;Ishibe et al, 2018;see below).…”
Section: Overview Of Mirna Abundance In Ad Tissues and Biofluid Compamentioning
confidence: 99%